Sodium-ion electrochemical tuning of Prussian blue analog as an efficient oxygen evolution catalyst. (June 2019) - Tang, S.; Li, L.; Ren, H.; Lv, Q.; Lv, R.
Abstract: Developing efficient and low-cost electrocatalysts for oxygen evolution reaction (OER) is crucial for hydrogen production by water splitting. Besides striving to explore catalysts with new compositions and structures, developing efficient tuning strategy to improve the performance of existing catalysts is of vital importance as well. Here, a sodium-ion electrochemical tuning method is proposed to improve the oxygen evolution catalytic activity of Prussian blue analog (PBA) hexacyanoferrate by tuning the oxidation states and defects in PBA structures. Compared with pristine PBA, the modified catalysts show a significant improvement in OER catalysis, with a decreased Tafel slope from 69 mV/dec to 41 mV/dec and an overpotential drop of 50 mV at 5 mA/mF. This work may promote the application of PBA in OER catalysis and more importantly provide a simple and effective strategy on tuning oxidation state and defects in material microstructures. Highlights: Discharge potential tunes the oxidation states of nickel-hexacyanoferrate (NiHCF) in sodium-ion batteries. Long cycles of charge–discharge process introduce defects and disorders into NiHCF crystal structures. Modified NiHCF shows improved oxygen evolution reaction catalytic activity.